Decision Support System Using Fuzzy Image Classification for Diagnosis of Knee Injuries - Naveen Dalal (International Journal of Intelligent Systems and Applications in Engineering, 2021)
Manual analysis of medical images is quite complicated and time consuming process and its outcomes highly depend over the experience of practitioners. Improper analysis of the patient’s data may lead to false diagnosis. In order to overcome from this issue, a fuzzy based decision support system will be presented in this paper. Injury will be detected on the basis of weighted classification and finally, this data will be provided to multi-agent-fuzzy interference engine for final decision making and diagnosis recommendation.